ASCOTT SERVICED APARTMENTS' MARKETING STRATEGY: CONSUMPTION TRENDS OF SHANGHAI'S NEW MIDDLE CLASS - Hongyang, Wang; Andayani, Ni Luh Henny; Heryanda, Komang Krisna (Distribusi - Journal of Management and Business, 2026)
Amid the rapid expansion of China’s emerging middle class and the upgrading of urban residential consumption, serviced apartments are transforming from functional accommodation products into lifestyle-oriented living spaces. Taking Ascott Serviced Residences in Shanghai as a case study, this research examines how marketing strategies can better align with the consumption psychology, behavioral preferences, and decision-making patterns of the new middle class. Drawing on STP theory, the 4P marketing mix, the VALS lifestyle model, and the five-dimensional experiential marketing framework, the study employs questionnaire surveys, empirical analysis, and competitive benchmarking to evaluate the effectiveness of Ascott’s current strategies. The findings reveal a mismatch between standardized product offerings and diversified, experience-driven user demands, as well as limitations in pricing flexibility, digital channels, and community engagement. Sensory and emotional experiences significantly influence initial stay decisions, while relational experiences drive repeat consumption. This study proposes a localized, experience-oriented marketing optimization framework, offering practical implications for serviced apartment brands seeking differentiated competition and sustainable brand value enhancement in emerging urban markets